Colorectal Surgical Site Infection Prevention Kits Prior to Elective Colectomy Improve Outcomes. Issue 6 (June 2020) - Deery, Sarah E.; Cavallaro, Paul M.; McWalters, Sean T.; Reilly, Syrene R.; Bonnette, Holly M.; Rattner, David W.; Mort, Elizabeth A.; Hooper, David C.; del Carmen, Marcela G.; Bordeianou, Liliana G.
Abstract : Introduction: Patient compliance with preoperative mechanical and antibiotic bowel preparation, skin washes, carbohydrate loading, and avoidance of fasting are key components of successful colorectal ERAS and surgical site infection (SSI)-reduction programs. In July 2016, we began a quality improvement project distributing a free SSI Prevention Kit (SSIPK) containing patient instructions, mechanical and oral bowel preparation, chlorhexidine washes, and carbohydrate drink to all patients scheduled for elective colectomy, with the goal of improving patient compliance and rates of SSI. Methods: This was a prospective data audit of our first 221 SSIPK+ patients, who were compared to historical controls (SSIPK−) of 1760 patients undergoing elective colectomy from January 2013 to March 2017. A 1:1 propensity score system accounted for nonrandom treatment assignment. Matched patients' complications, particularly postoperative infection and ileus, were compared. Results: SSIPK+ (n = 219) and SSIPK− (n = 219) matched patients were statistically identical on demographics, comorbidities, BMI, surgical indication, and procedure. SSIPK+ patients had higher compliance with mechanical (95% vs 71%, P < 0.001) and oral antibiotic (94% vs 27%, P < 0.001) bowel preparation. This translated into lower overall SSI rates (5.9% vs 11.4%, P = 0.04). SSIPK+ patients also had lower rates of anastomotic leak (2.7% vs 6.8%, P = 0.04), prolonged postoperative ileus (5.9% vs 14.2%, P < 0.01), and unplanned intubation (0% vs 2.3%, P = 0.02). Furthermore, SSIPK+ patients had shorter mean hospital length of stay (3.1 vs 5.4 d, P < 0.01) and had fewer unplanned readmissions (5.9% vs 14.6%, P < 0.001). There were no differences in rates of postoperative pneumonia, urinary tract infection, Clostridium difficile colitis, sepsis, or death. Conclusion: Provision of a free-of-charge SSIPK is associated with higher patient compliance with preoperative instructions and significantly lower rates of surgical site infections, lower rates of prolonged postoperative ileus, and shorter hospital stays with fewer readmissions. Widespread utilization of such a bundle could therefore lead to significantly improved outcomes. Abstract : Supplemental Digital Content is available in the text